The use of pectins from the bark of coniferous trees in canned food production - E. A. Medvedeva; L. K. Patsyuk; N. M. Alabina; T. V. Nariniyants (Аграрная наука Евро-Северо-Востока, 2018)
The article deals with the possibility of utilization of pectins from the bark of coniferous tree species for the manufacture of fruit and vegetable canned goods (jelly, jam and nectars with pulp) as biological additives that improve product consistency. Due to their unique properties, pectin substances are widely used in modern conditions and can be used as an additive in the production of food products. In the food industry, of particular importance are such properties of pectin substances as gelling, structure-forming and thickening abilities, which is very important when creating food products with certain structural characteristics. Experimental samples of fruit jams with the introduction of different amounts of pectin to thicken the product (0.3%, 0.5%, 0.8%, 1.0%) were put out. During the sensor analysis of these jams the best characteristics were obtained by samples, into which pectin from the bark of spruce in an amount of 1.0% was added. The possibility of using pectins from the bark of spruce and larch as gelling agents in the manufacture of jelly was investigated. Composite mixtures which produced three versions of the jelly images with pectin were developed: No.1 - control with apple pectin; No. 2 - with pectin from the spruce bark; No. 3 - with pectin from the larch bark. It has been established that the organoleptic characteristics of the sample No.2 differ from the control sample slightly. Sample No. 3 has received non-satisfactory rating in all organoleptic parameters. To confirm the structure-forming ability of pectin from spruce bark, the samples of nectars with pulp with addition of pectin from spruce bark are manufactured. The expediency of using this pectin is 0.9%.